War during the COVID-19 Pandemic: Case between Israel and Palestine - Yordan Gunawan; Kania Dewi; Gladis Tazaka Mustaqim; Mohammad Hazyar Arumbinang (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this article is to find out how international law plays a role in the Israeli-Palestinian war during the Covid-19 pandemic. The method in writing this article was a literature study by collecting literature from journals and books relevant to the topic, then analyzing it, and then making conclusions. The emergence of the Covid-19 pandemic that spreads rapidly raises concerns about the socio-economic conditions of Palestinian citizens. The challenge is getting bigger in tackling these two problems simultaneously. The condition of Palestinian citizens is increasing concerning with the destruction of WASH facilities (water, sanitation, and hygiene), the inhibition of the supply of necessities that will enter the Palestinian state, as well as the destruction of the natural environment since these aspects can be used to prevent the spread of the Covid-19 virus. International humanitarian law actually exists to limit the occurrence of such incidents, but these regulations are violated by the military and the Israeli government. This article is helpful to find out how the actions of the state of Israel against Palestine during the Covid-19 pandemic are based on the perspective of international law. This article was compiled with references to various literary sources from national and international journals and books. In addition, it also uses the latest news from the topics discussed. The result of this literature study is that the conflict that is being experienced by Israel and Palestine is not getting better with the increasing number of attacks on Palestinian civilians.